2011
DOI: 10.2174/092986711797189637
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Based Fluorescent Biosensors

Abstract: Selected from random pools of DNA or RNA molecules through systematic evolution of ligands by exponential enrichment (SELEX), aptamers can bind to target molecules with high affinity and specificity, which makes them ideal recognition elements in the development of biosensors. To date, aptamer-based biosensors have used a wide variety of detection techniques, which are briefly summarized in this article. The focus of this review is on the development of aptamer-based fluorescent biosensors, with emphasis on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(109 citation statements)
references
References 101 publications
(120 reference statements)
0
108
0
1
Order By: Relevance
“…The RNA scaffold has a restriction site in which any nucleic acid material can be inserted 25 . Furthermore, DNA/RNA aptamers specific for an increasing number of targets are now available, and it has been shown that it is possible to rationally convert non-fluorescent aptamers into fluorescent reporters 26 . It has also been shown that fluorescent aptamers can be selected directly from random sequence DNA libraries in vitro 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The RNA scaffold has a restriction site in which any nucleic acid material can be inserted 25 . Furthermore, DNA/RNA aptamers specific for an increasing number of targets are now available, and it has been shown that it is possible to rationally convert non-fluorescent aptamers into fluorescent reporters 26 . It has also been shown that fluorescent aptamers can be selected directly from random sequence DNA libraries in vitro 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their high selectivity, stability, versatile target binding and easy regeneration capabilities over antibodies, aptamers have received considerable research attention as recognition probes in biodetections. Various aptamer-based biodetection schemes for biomolecules including fluorescence (Wang, Zhang, Cai, Cai, & Gao, 2011), electrochemistry (Chen, Yao, Xie, & Liu, 2014), surface plasma resonance (Tang, Su, & Loh, 2007), and chemiluminescence (Shim et al, 2014) have been demonstrated. Among these detection schemes, the fluorescencebased approach has attracted increasing interest due to its advantages in terms of simplicity, high sensitivity and good reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…They possess a typical stem-loop structure, which is disrupted by target association, resulting in the separation of the fluorophore-quencher pair [25]. A comprehensive description of the various types of aptamer sensors and their applications has been covered by several recent reviews [15,[26][27][28].…”
Section: Nucleic Acid-based Biosensorsmentioning
confidence: 99%